Knowledge and application of standards of radiological protection, biosafety and health risks in students of the Academy. - Barros-Astudillo , Teodoro (2023)
Introduction: Health professionals, particularly radiologists and imaging scientists are exposed to increased radiological risks. The standards and protocols for radiological protection and biosafety are of great importance since they contribute to avoiding deterministic and/or stochastic effects and contamination. Objective: Determine the level of knowledge and application of the standards of radiological protection, biosafety and possible health risks of undergraduate students who carry out pre-professional practices of the Radiology Career. Material and methods: Descriptive, observational, and cross-sectional study; sample of 58 undergraduate students. The instrument used was: a survey of students and heads of the Radiology service. Statistical analyses were descriptive and Pearson's Chi2 test of independence was used. Results: Students indicate that there are radiation protection standards in Imaging services (82.8%); Its application corresponds to: distance (84.5%), time (70.7%) and shielding (62.1%) and the use of the dosimeter (51.7%). The best knowledge is: types of radiological protection (94.8%), dosimetry (67.2%) and deterministic effects (77.6%); those with the lowest percentage: stochastic effects (60.3%) and whole-body radiation dose limits (43.1%). Risks: direct contact with body fluids (74.1%), use of secondary barriers (70.7%), handling of radiopharmaceuticals (62.1%) and dose rate allowed for Occupationally Exposed Personnel (51.7 %); lower risks: distance (75.9%), time (74.1%), use of primary barriers (65.5%), hand washing (62.1%) and use of the dosimeter (62.1%) Discussion: The knowledge and practice of radiation protection and biosafety standards is partial among students and possible health risks are latent.